Spectral tuning of IR-resonant nanoantennas by nanogap engineering - Weber, Daniel; Katzmann, Julia; Neubrech, Frank; Härtling, Thomas; Pucci, Annemarie (Optical materials express, 2011)
We report on tuning the plasmonic properties of gold nanoantenna arrays resonant in the infrared (IR) spectral region. In particular, we achieve a manipulation of the antenna resonance by decreasing the antenna separation distance via photochemical metal deposition. Narrowing the antenna gaps is monitored using scanning electron microscopy, while increased plasmonic coupling and an associated red-shift of the plasmon resonance is observed by microscopic IR spectroscopy. Since smaller gap sizes lead to enhanced electric fields between the antenna arms, we propose photochemical metal deposition as a fabrication step for surface-enhanced IR spectroscopy (SEIRS) substrates.
Gesehen am 09.11.2022